A Characterization for the Deformation Behavior of As-Cast P91 Alloy Steel and Utilization in Hot Extrusion Process - Lu Jia; Yongtang Li; Yang Zhang (Advances in Materials Science and Engineering)
The constitutive models of as-cast P91 alloy steel were investigated by unidirectional thermal compression tests, which were conducted over a wide range of temperature and strain rate on Gleeble-3500 thermal simulation machine. The constitutive models were coupled with finite element method to simulate the hot extrusion process. Furthermore, the industrial hot extrusion experiment on actual pipe was conducted on 500 MN vertical extrusion machine and the load-displacement data during the extrusion were recorded. Comparisons between the numerical simulation and industrial experimental results were carried out and confirmed that the developed constitutive models can be used in the simulation and industrial research of compact hot extrusion process.